The effect of BEMER therapy on selected blood indicators in the process of biological restitution after exercise endurance. A case study - Mrozkowiak, Mirosław; Posłuszny, Mariusz (Journal of Education, Health and Sport, 2017)
Introduction. Microcirculation vessels comprise 99% of blood vessels in an adult human body11. Capillary network density in particular tissues grows proportionally to their oxygen demand. BEMER therapy, used as complex or supplementary treatment, improves basic physiological processes, angiokinesis, microcirculation, as well as oxygenation and nutrition of muscle cells. Due to particular biorythmic modulation, it exerts synergic influence on primary and secondary, slightly bigger, blood vessels. Materials and methods. The study was conducted on a male individual who leads a healthy life style and who twice subjected himself to the markings of cognitive functions and selected blood indicators; first, during natural physiological restitution after endurance exercise, and second, after restitution enhanced with BEMER therapy. Results. Most significant changes after exercise endurance were observed in the following blood indicators: leukocytes, erythrocytes, insulin and cortisol. Least significant changes were noted in the number of lymphocytes and in cognitive functions. Conclusions. Applied methodology and profile of BEMER signal variously affects selected blood indicators. Application of BEMER stimulation in the process of restitution after endurance exercise in men in their fifties / sixties may be justified.